2019
DOI: 10.1590/s0102-053620190102
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of wild Solanaceae rootstocks to the parasitism of (Meloidogyne javanica)

Abstract: Intensive production of vegetables in greenhouses can increase the amount of inoculum of soil-borne pathogens, such as the root-knot nematode. Thus, in this study we aimed to evaluate the potential of Solanaceae as rootstocks resistant to Meloidogyne javanica nematodes as an alternative to tomato grafting. The experiment consisted of seven treatments: wild species joá-vermelho (Solanum capsicoides), joá-bagudo (Solanum palinacanthum), joá-bravo (Solanum viarum), jurubeba (Solanum spp.) and the commercial tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The field trials also demonstrated that the nematode population densities in the soil after growing S. palinacanthum were significantly lower than those after growing susceptible plants under field conditions. To the best of our knowledge, RKN‐resistance of S. palinacanthum was reported only by Carsodo et al ., 24 in which S. palinacanthum showed M. javanica ‐resistance.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The field trials also demonstrated that the nematode population densities in the soil after growing S. palinacanthum were significantly lower than those after growing susceptible plants under field conditions. To the best of our knowledge, RKN‐resistance of S. palinacanthum was reported only by Carsodo et al ., 24 in which S. palinacanthum showed M. javanica ‐resistance.…”
Section: Discussionmentioning
confidence: 83%
“…18,19 This plant has been studied exclusively for its metabolites and chemical components intended for medical or pharmaceutical use, [20][21][22][23] and there are few studies of its use in agriculture, such as host resistance for phytophagous nematode control. 24 We conducted the present study to evaluate host suitability for the most important species of RKN in Japan (M. incognita, M. arenaria genotypes A2-J and A2-O, M. javanica, and M. hapla) on S. palinacanthum, and to test the effectiveness of the resistance by cultivating S. palinacanthum under field conditions infested with natural populations of RKN. In general, M. arenaria is divided into types A1, A2, and A3 by isozyme patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wild Solanum plant Solanum palinacanthum was recently found to be resistant to RKN (Cardoso et al, 2019;Murata et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This plant has been studied mainly for medical and pharmaceutical use (Almeida et al, 2010;Bouzada et al, 2009;Matias et al, 2016;Moreira et al, 2013), whereas its usefulness in agriculture is poorly understood. Using self-rooted plants in pot and/or field trials, Cardoso et al (2019) and Murata et al (2020) reported that S. palinacanthum suppressed M. incognita, M. arenaria, M. javanica and M. hapla, indicating that S. palinacanthum is useful for RKN management and it can also be used as rootstock for Solanum plants.…”
Section: Solanum Palinacanthum Dunal Is a Minor Crop Distributed In S...mentioning
confidence: 99%